TOUR VIRTUAL SEBAGAI SARANA PENGGANTI LIBURAN DI MASA PANDEMIC COVID 19 - Renny Christiarini; Amanda Rosetia; Nur Hidayati; Nicky Adi Putra; Chicha Rosha; Estina Sativa; Dea Punjung Sari; Dewirahayu Sad Wijaya; Getri Bela Saputri; Raka Prasetya; Sherly Marlina (National Conference for Community Service Project (NaCosPro), 2020)
Due to the pandemic COVID-19, the government made a regulation called lockdown. This aims to decrease the spreading of COVID-19. Since lockdown had started, people felt so bored where stayed at home for a quiet long period. As a consequence, we realized that people need to go on holiday. We tried to solve the problem by making a virtual tour video. In this case, a virtual tour video is a video recording in which the content is about the tourist attraction that could be watched by viewers. The methods which relevant we used are interview and observation. After doing the survey, we found that the interviewers had pretty satisfied with the video. The implication of the next survey is to increase the virtual tour video’s quality.